PEMBUATAN COOKIES BERSERAT TINGGI DENGAN MEMANFAATKAN TEPUNG AMPAS MANGROVE (Sonneratiacaseolaris) - Sarofa, Ulya; Mulyani, Tri; Wibowo, Yudda Arief (UPN VETERAN JAWA TIMUR, 2011)
Demand of health food products such as sugar-free foods, low-calorie diet and fiber-rich increased. This trend is based on the role of prevention of hypertension, diabetes, colon cancer and other degenerative diseases. Various sources of high-fiber materials such as cellulose, hemicellulose, lignin, and gum were a major concern in the development of food products. Therefore, the utilization of mangrove waste of syrup processing to yield a high fiber cookies was important made. This study aims to determine the proportion of wheat and mangrove waste flour, the addition of margarine on the quality of cookies. This study using Complete Randomized Design (CRD) factorial pattern with 2 factors and 3 replications. Factor I, proportioni wheat flour: mangrove waste 15:85 (w/w), 30:70 (w/w), 45:55 (w/w). Factor II,the addition of margarine 40% (v/w), 45% (v/w), and 50% (v/w). The results showed that the best treatment was the proportion of wheat : mangrove waste flour 30:70 (w/w) and the addition of margarine 45% (v/b) which it produces cookies with the criteria of 3.9343% moisture content, protein 6.2745%, fat 22.4180%, and crude fiber value of 3.4456%.Key words: cookies, mangrove waste, health food products